IMPACT OF PILGRIMAGE TOURISM TO THE SHEIKH QURO’S TOMB KARAWANG ON THE LOCAL COMMUNITY QUALITY OF LIFE - Puspita, Nungky; Gunadi, I Made Adhi; Nuradawiah, Lita (Institut Pariwisata dan Bisnis Internasional, 2019)
Pilgrimage tour of Syekh Quro is the religious tour in Karawang located in Pulobata, Pulokalapa village, Lemahabang Wadas district, Karawang regency, West Java Province. This reseach is aimed to identify the impact of the religious tour activity of Syekh Quro’s Tomb toward local society quality of life. The research method used in this research is descriptiv qualitative. The finding showed that the tourism impact toward local society quality of life clarify that pilgrimage tourism give positive impact on Pulobata communities. These positive impacts are seen on the aspects of material wellbeing, community wellbeing, emotional wellbeing, and health and safety wellbeing.